Er-Zr microalloyed AlSi10Mg alloy powder material and preparation method thereof as well as aluminum alloy workpiece and preparation method thereof

By adding Er and Zr to the AlSi10Mg alloy to form a specific combination, the problem of insufficient mechanical properties of aluminum alloy parts is solved, and its tensile strength and elongation are significantly improved, meeting the application needs of high load-bearing stress.

CN119177378AInactive Publication Date: 2024-12-24CHINALCO RES INST OF SCI & TECH CO LTD

Patent Information

Application Number
CN202411681227.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2024-12-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing AlSi10Mg aluminum alloy parts have poor mechanical properties and cannot meet the application of structural parts with high load-bearing stress.

Method used

By using Er-Zr microalloyed AlSi10Mg alloy powder, the Al3Er phase and L12Al3 (Er, Zr) phase are formed by controlling the content of Si, Mg, Er and Zr elements, thereby promoting the formation and refinement of equiaxed crystals and improving the grains. Tensile strength, yield strength and elongation of aluminum alloy parts.

Benefits of technology

The mechanical properties of aluminum alloy parts have been significantly improved, with tensile strength reaching 451.6MPa~482.7MPa, yield strength of 293.4MPa~329.7MPa, elongation of 4.1%~8.7%, meeting the application needs of structural parts with high load-bearing stress.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119177378A_ABST
    Figure CN119177378A_ABST
Patent Text Reader

Abstract

The invention provides an Er-Zr microalloyed AlSi10Mg alloy powder material, a preparation method of the Er-Zr microalloyed AlSi10Mg alloy powder material, an aluminum alloy workpiece and a preparation method of the aluminum alloy workpiece. The Er-Zr microalloyed AlSi10Mg alloy powder material comprises the following elements in percentage by mass: 9.50 to 10.60 percent of Si element, 0.35 to 0.55 percent of Mg element, 0.70 to 1.30 percent of Er element, 0.70 to 1.30 percent of Zr element, less than or equal to 0.15 percent of total content of inevitable impurities, less than 0.05 percent of single impurity and the balance of Al element. And the Zr element and the Er element can form a dynamically stable L12Al3 (Er, Zr) phase, and the second phase strengthening effect and the recrystallization inhibition effect are achieved, so that the mechanical property of the aluminum alloy workpiece is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aluminum alloys, and in particular to an Er-Zr microalloyed AlSi10Mg alloy powder material and a preparation method thereof, an aluminum alloy product and a preparation method thereof. Background Art

[0002] Compared with traditional processing technologies such as casting, forging, extrusion, welding, and machining, metal additive manufacturing technology, which features direct manufacturing of complex structures and integrated forming of high-performance material preparation, is subverting the traditional design and manufacturing methods of high-end equipment to form unprecedented innovative solutions, providing rapid development opportunities for the design and forming of complex structural parts and the design and development of high-performance alloys. Lightweight aluminum alloy complex structural parts with excellent mechanical properties have received extensive attention in the fields of aerospace, automotive, and national defense industries. At the same time, with the continuous maturity and standardization of additive manufacturing technology, the quality requirements and technical thresholds of aluminum alloy powders for additive manufacturing are also constantly improving. New aluminum alloy materials are showing a rapid development trend, and higher strength has become the next generation of opportunities to support additive manufacturing technology.

[0003] Although the wide application of high-strength aluminum alloys has promoted the rapid development of aluminum alloy additive manufacturing technology, it has led to different process constraints faced by material design. At present, it is subject to material problems: first, traditional aluminum alloys tend to form coarse, textured columnar grains during rapid non-equilibrium solidification, leading to problems such as thermal cracks and performance anisotropy and cannot be directly applied; second, the strength of mainstream aluminum alloys for additive manufacturing is difficult to reach the level of forged high-strength aluminum alloys, limiting their service scenarios.

[0004] As the most important basic raw material for metal additive manufacturing, powder is an important part of the additive manufacturing industry chain. Its quality has a key impact on the stability of the additive manufacturing process, forming precision and product quality stability. Although the powder properties applicable to different additive manufacturing processes are different, the basic requirements are stable composition, high purity, narrow particle size distribution, high sphericity, low hollow powder rate, low oxygen content, etc. At the same time, the current powder yield of aluminum alloy powder for laser additive manufacturing is low, at about 30%~35%. In order to meet the requirements of engineering production and application, it is necessary to improve the yield of atomized powder. In addition, during the printing process, inappropriate manufacturing parameters will also introduce defects related to geometry, surface integrity and microstructure, which will lead to anisotropy of mechanical properties and reduce the strength, ductility and other mechanical properties of the formed material. Therefore, the aerosol preparation method of aluminum alloy powder for laser additive manufacturing and the additive manufacturing method are crucial.

[0005] The Chinese patent application with the patent application publication number CN117862525A proposes an AlSi10Mg-Er alloy additive material and a preparation method thereof, the preparation method comprising the following steps: laying AlSi10Mg composite powder containing 0.4wt.%-0.6wt.% Er on the substrate of the forming chamber to form an alloy powder layer; and performing laser scanning and melting forming on the alloy powder layer layer by layer under the protection of an inert gas. The AlSi10Mg-Er alloy additive material has a refined grain after rare earth Er is added. The mechanical properties of the AlSi10Mg-Er alloy will be further improved after aging treatment. The performance of the printed part is: tensile strength 426MPa~465MPa; and / or, yield strength 305MPa~337MPa; and / or, elongation 8.6%~9.7%. After failure treatment, the properties of the AlSi10Mg-Er alloy additive are: tensile strength 450MPa~465MPa; and / or, yield strength 323MPa~337MPa; and / or, elongation 8.6%~9.0%. However, the strength of the AlSi10Mg-Er alloy additive prepared by this method is relatively low.

[0006] The Chinese patent application with the patent application publication number CN107716918A proposes an AlSi10Mg powder material for 3D printing and a preparation method thereof. The mass fraction of the main alloy elements in the powder material is: Si is 9.0~11.5%, Mg is 0.2~0.50%, and the balance is aluminum. The powder material is prepared by an inert gas atomization method, and a high-speed airflow is used to break the high-temperature molten liquid of the powder material into small droplets and then rapidly cooled to solidify it into a metal powder. The obtained metal powder is sieved and graded for particle size. The AlSi10Mg powder material meets the quality requirements of industrial-grade metal 3D printing powder materials, and has the advantages of high purity, low impurity content, uniform alloy composition, low oxygen content; high sphericity, few satellite balls; uniform powder particle size distribution, controllable quality, and excellent powder performance. The tensile strength of its printed parts is ≥400MPa, the yield strength is ≥250MPa, and the elongation is ≥8.5%. However, the strength of the printed parts prepared by this method is relatively low.

[0007] The Chinese patent application with the patent application publication number CN106868353A proposes a scandium-containing aluminum powder alloy, a wire and a material containing the alloy, and a method for producing the scandium-containing aluminum powder alloy, the wire and the material. The proportion of scandium in the scandium-containing aluminum powder alloy is increased to not less than 0.6% and up to 30%. The addition of a high content of Sc element increases the cost of the alloy powder, which is 3 to 4 times the price of Al-Si alloy powder, which limits its wide application in low-cost civilian fields. However, the high price of Sc makes it difficult to promote and apply, and the precipitation driving force is small.

[0008] The Chinese patent application with the patent application publication number CN112048647A proposes an Al-Si-Mg-Sc-Zr aluminum alloy powder for laser additive manufacturing and its application. The aluminum alloy powder for laser additive manufacturing has the following components by mass fraction: Si: 6.0~8.0%, Mg: 0.60~0.80%, Ti: 0.10~0.20%, Sc: 0.1~0.6%, Zr: 0.1~0.4%, and the remainder is Al and unavoidable impurities. The Al-Si-Mg-Sc-Zr aluminum alloy powder for laser additive manufacturing is powdered by gas atomization. The density of the sample formed by SLM of the Al-Si-Mg-Sc-Zr aluminum alloy powder can reach more than 99.9%, the tensile strength of the deposited sample exceeds 440MPa, the elongation after fracture of the sample after heat treatment exceeds 10%, and there is no obvious anisotropy, which can meet the needs of applications in related fields. However, the high price of Sc makes it difficult to promote and apply, and the precipitation driving force is small.

[0009] The mechanical properties of Al-Si alloy systems are usually regulated by composition modification based on stoichiometric changes, addition of strengthening particles or microalloying. Although the refinement of the eutectic network structure, the narrowing of the temperature range of alloy solidification and the use of solid solution strengthening to enhance the mechanical properties can be induced by changing the Si and Mg contents, the content regulation is limited, otherwise a high crack density will be generated. The high-strength Al-Si alloys currently introduced for additive manufacturing mainly improve their mechanical properties by in-situ regeneration or Sc microalloying. By adding strengthening particles such as ceramics and carbon-based materials, in-situ generation of heterogeneous nucleation particles is used to increase the nucleation rate and pin the grain boundaries to limit the growth of α-Al, and the transformation of columnar crystals to equiaxed crystals is promoted to reduce the tendency of hot cracking. Although the tensile strength is enhanced, the introduction of strengthening particles by mixing powders may cause uneven particle distribution and destruction of powder morphology, and composition segregation is difficult to avoid, resulting in defects and anisotropy of properties. In addition, the density difference between the strengthening particles and the aluminum matrix, the wettability matching problem and the reactivity will lead to the obstruction of the atomization process, the formation of defects and the loss of strengthening particles. Microalloying based on the rare earth element Sc can avoid the above problems. The modification and refinement of Sc on α-Al crystals and eutectic Si structures and the second phase strengthening effect of the nano-precipitated phase during heat treatment can promote the nucleation of equiaxed crystals during alloy solidification, thereby obtaining an ultrafine eutectic structure and significantly improving the mechanical properties. However, the expensive price and small reserves of Sc increase the preparation cost and limit its large-scale industrial application. In addition, the maximum solid solubility of Sc in the equilibrium state is 0.35%, which limits its maximum precipitation strengthening effect.

[0010] Among many aluminum alloy systems, the Al-Si alloy system is currently the most suitable aluminum alloy for laser additive manufacturing due to its low melting point and narrow solidification temperature range. It is mainly represented by near-eutectic alloys such as A1Si10Mg, AlSi7Mg and AlSi12. For this type of alloy, research work mainly focuses on the optimization of additive manufacturing process parameters, but the mechanical properties of the Al-Si alloy material itself are poor, with a tensile strength of only 300MPa and a yield strength of only 200MPa. Although it can be used for general applications, it cannot meet the requirements for high-stress structural parts. Therefore, it is urgent to develop a new low-cost AlSi10Mg alloy powder to expand the application range of laser additive printing parts. Summary of the invention

[0011] The main purpose of the present invention is to provide an Er-Zr microalloyed AlSi10Mg alloy powder and a preparation method thereof, an aluminum alloy product and a preparation method thereof, so as to solve the problem of poor mechanical properties of AlSi10Mg aluminum alloy products in the prior art.

[0012] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, there is provided an Er-Zr microalloyed AlSi10Mg alloy powder, which comprises the following elements, in terms of mass percentage: Si element content is 9.50-10.60%, Mg element content is 0.35-0.55%, Er element content is 0.70-1.30%, Zr element content is 0.70-1.30%, the total content of inevitable impurities is ≤0.15wt%, the content of a single impurity is less than 0.05wt%, and the balance is Al element.

[0013] Further, the mass ratio of the above-mentioned Er element to Zr element is 1:0.65~1; and / or, the content of oxygen in the Er-Zr microalloyed AlSi10Mg alloy powder is ≤460ppm; and / or, the content of nitrogen in the Er-Zr microalloyed AlSi10Mg alloy powder is ≤15ppm; and / or, the sphericity of the Er-Zr microalloyed AlSi10Mg alloy powder is ≥80%; and / or, the hollow powder rate of the Er-Zr microalloyed AlSi10Mg alloy powder is ≤0.54%; and / or, the volume fraction of the Er-Zr microalloyed AlSi10Mg alloy powder in the particle size range of 0~75μm is more than 97%, and the D10 of the Er-Zr microalloyed AlSi10Mg alloy powder is 20~27μm, D50 is 35~40μm and D90 is 60~67μm.

[0014] According to another aspect of the present invention, a method for preparing the aforementioned Er-Zr microalloyed AlSi10Mg alloy powder is provided, the preparation method comprising: smelting, refining and atomizing various raw materials including metals in accordance with a proportion to obtain Er-Zr microalloyed AlSi10Mg alloy powder.

[0015] Furthermore, the smelting temperature is 850°C to 950°C; and / or the smelting time is 15min to 30min; and / or the refining temperature is 850°C to 950°C; and / or the refining time is 10min to 15min; and / or the atomization temperature is 850°C to 900°C; and / or the atomization pressure is 2.3MPa to 2.8MPa; and / or the atomization speed is 10 to 14Kg / min.

[0016] According to another aspect of the present invention, a method for preparing an aluminum alloy part is provided, the method comprising: sequentially performing 3D printing and heat treatment on the aforementioned Er-Zr microalloyed AlSi10Mg alloy powder to obtain the aluminum alloy part.

[0017] Furthermore, the pressure of the above-mentioned 3D printing is 23mbar~27mbar; and / or, the fan flow rate of 3D printing is 2.3m / s~2.7m / s; and / or, the preheating temperature of the substrate for 3D printing is 80~120℃; and / or, the thickness between printing layers of 3D printing is 20~50μm; and / or, the laser scanning spacing of 3D printing is 100~120μm; and / or, the interlayer rotation angle of 3D printing is 67°; and / or, the laser scanning power of 3D printing is 260W~340W; and / or, the laser scanning speed of 3D printing is 1400mm / s~1800mm / s; and / or, 3D printing is carried out in an atmosphere with an oxygen content not exceeding 0.08%.

[0018] Furthermore, the temperature of the heat treatment is 165°C to 280°C; and / or the heat treatment holding time is 2h to 4h.

[0019] Furthermore, the density of the printed part obtained by 3D printing is not less than 99.95%; and / or the tensile strength of the printed part is 451.6MPa~482.7MPa; and / or the yield strength of the printed part is 293.4MPa~329.7MPa; and / or the elongation of the printed part is 4.1%~8.7%.

[0020] According to another aspect of the present invention, there is provided an aluminum alloy part, which is prepared by the aforementioned preparation method.

[0021] Furthermore, the tensile strength of the aluminum alloy part is 321.6 MPa to 483.0 MPa; and / or, the yield strength of the aluminum alloy part is 210.2 MPa to 311.0 MPa; and / or, the elongation of the aluminum alloy part is 6.9% to 19.5%.

[0022] By applying the technical solution of the present invention, the contents of Si, Mg, Er and Zr in the Er-Zr microalloyed AlSi10Mg alloy powder of the present application are controlled within a suitable range, which helps to improve the mechanical properties of the aluminum alloy parts finally formed, especially the content of Er is controlled within 0.70-1.30%, the content of Zr is controlled within 0.70-1.30%, and the rare earth element Er has a small solid solubility in the Al matrix, and is repelled to the front end of the solid-liquid interface during the crystallization process, resulting in enrichment. The enrichment of the rare earth element Er at the solid-liquid interface helps to reduce the probability of Si and Mg atoms entering the solid solution, thereby helping to inhibit the growth of the unit cell. In addition, the Er element enriched at the front end of the solid-liquid interface reacts eutectically with Al to form an Al3Er phase during the subsequent solidification process. At the same time, the smaller solid solubility of Er in the aluminum matrix indicates that Al3Er has a stronger precipitation driving force, so that it can precipitate a larger volume fraction. The Al3Er phase has a high melting point and will not completely melt during the remelting process at a relatively low temperature at the molten pool boundary. It can act as a heterogeneous nucleation point to promote the formation of equiaxed crystals and refine grains, thereby helping to improve the tensile strength, yield strength and elongation of aluminum alloy parts. The Zr element can form a kinetically stable L12Al3 (Er, Zr) phase with the Er element, which has a second phase strengthening effect and a recrystallization inhibition effect, thereby helping to further improve the mechanical properties of aluminum alloy parts. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0024] Figure 1 The SEM image of the Er-Zr microalloyed AlSi10Mg alloy powder in Example 1 of the present application is shown;

[0025] Figure 2 The SEM image of the Er-Zr microalloyed AlSi10Mg alloy powder in Example 2 of the present application is shown. DETAILED DESCRIPTION

[0026] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0027] As analyzed in the background technology of this application, the existing technology has the problem of poor mechanical properties of AlSi10Mg aluminum alloy parts. In order to solve the above problems, this application provides an Er-Zr microalloyed AlSi10Mg alloy powder and a preparation method thereof, an aluminum alloy part and a preparation method thereof.

[0028] In a typical embodiment of the present application, an Er-Zr microalloyed AlSi10Mg alloy powder is provided. The Er-Zr microalloyed AlSi10Mg alloy powder comprises the following elements, measured in mass percentage: Si element content is 9.50~10.60%, Mg element content is 0.35~0.55%, Er element content is 0.70~1.30%, Zr element content is 0.70~1.30%, the total content of unavoidable impurities is ≤0.15wt%, the content of a single impurity is less than 0.05wt%, and the balance is Al element.

[0029] In the Er-Zr microalloyed AlSi10Mg alloy powder of the present application, the contents of Si element, Mg element, Er element and Zr element are controlled within a suitable range, which helps to improve the mechanical properties of the aluminum alloy parts finally formed, especially the content of Er element is controlled at 0.70~1.30%, the content of Zr element is controlled at 0.70~1.30%, the rare earth element Er has a small solid solubility in the Al matrix, and is repelled to the front end of the solid-liquid interface during the crystallization process, resulting in enrichment. The enrichment of the rare earth element Er at the solid-liquid interface helps to reduce the probability of Si and Mg atoms entering the solid solution, thereby helping to inhibit the growth of the unit cell. In addition, the Er element enriched at the front end of the solid-liquid interface reacts eutectically with Al to form Al3Er phase during the subsequent solidification process. At the same time, the smaller solid solubility of Er in the aluminum matrix shows that Al3Er has a stronger precipitation driving force, so that it can precipitate a larger volume fraction. The Al3Er phase has a high melting point and will not completely melt during the remelting process at a relatively low temperature at the molten pool boundary. It can act as a heterogeneous nucleation point to promote the formation of equiaxed crystals and refine grains, thereby helping to improve the tensile strength, yield strength and elongation of aluminum alloy parts. The Zr element can form a kinetically stable L12Al3 (Er, Zr) phase with the Er element, which has a second phase strengthening effect and a recrystallization inhibition effect, thereby helping to further improve the mechanical properties of aluminum alloy parts.

[0030] In one embodiment of the present application, the mass ratio of the above-mentioned Er element to the Zr element is 1:0.65~1; and / or, the content of oxygen in the Er-Zr microalloyed AlSi10Mg alloy powder is ≤460ppm; and / or, the content of nitrogen in the Er-Zr microalloyed AlSi10Mg alloy powder is ≤15ppm; and / or, the sphericity of the Er-Zr microalloyed AlSi10Mg alloy powder is ≥80%; and / or, the hollow powder rate of the Er-Zr microalloyed AlSi10Mg alloy powder is ≤0.54%; and / or, the volume fraction of the Er-Zr microalloyed AlSi10Mg alloy powder in the particle size range of 0~75μm is more than 97%, and the D10 of the Er-Zr microalloyed AlSi10Mg alloy powder is 20~27μm, D50 is 35~40μm and D90 is 60~67μm.

[0031] It is preferred to control the mass ratio of Er element to Zr element within the above range, which helps to improve the interaction between the two and form more dynamically stable L12Al3 (Er, Zr) phases, thereby helping to further improve the mechanical properties of aluminum alloy parts. Oxygen and nitrogen elements with the above content help to reduce the probability of defects caused by oxidation in Er-Zr microalloyed AlSi10Mg alloy powder during 3D printing. Er-Zr microalloyed AlSi10Mg alloy powder with the above sphericity helps to improve the fluidity of Er-Zr microalloyed AlSi10Mg alloy powder during 3D printing, thereby helping to improve the bonding between layers of aluminum alloy parts. Er-Zr microalloyed AlSi10Mg alloy powder with the above hollow powder rate helps to reduce the probability of pores during 3D printing. Er-Zr microalloyed AlSi10Mg alloy powder with the above particle size distribution helps to improve the density of aluminum alloy parts.

[0032] In another typical embodiment of the present application, a method for preparing the aforementioned Er-Zr microalloyed AlSi10Mg alloy powder is provided, the preparation method comprising: smelting, refining and atomizing various raw materials including metals in accordance with a proportion to obtain Er-Zr microalloyed AlSi10Mg alloy powder.

[0033] Melting the various metal raw materials to form aluminum liquid helps to improve the dispersion uniformity between the elements. Refining helps to reduce the content of impurities in the aluminum liquid. Atomization can prepare Er-Zr micro-alloyed AlSi10Mg alloy powder with suitable sphericity and particle size distribution, which helps to improve the density of aluminum alloy parts, thereby helping to improve the mechanical properties of aluminum alloy parts.

[0034] The raw materials of the above metals include pure aluminum, pure magnesium, aluminum-silicon master alloy, aluminum-erbium master alloy and aluminum-zirconium master alloy. Among them, the purity of pure aluminum and pure magnesium is ≥99.99%; the mass percentage of silicon in the aluminum-silicon master alloy is 20%, and the purity is ≥99%; the mass percentage of erbium in the aluminum-erbium master alloy is 5%, and the purity is ≥99%; the mass percentage of zirconium in the aluminum-zirconium master alloy is 10%, and the purity is ≥99%; and the mass percentage of manganese in the aluminum-manganese master alloy is 10%, and the purity is ≥99%.

[0035] In one embodiment of the present application, the above-mentioned smelting temperature is 850°C~950°C; and / or, the smelting time is 15min~30min; and / or, the refining temperature is 850°C~950°C; and / or, the refining time is 10min~15min; and / or, the atomization temperature is 850°C~900°C; and / or, the atomization pressure is 2.3MPa~2.8MPa; and / or, the atomization speed is 10~14Kg / min.

[0036] Preferably, the smelting temperature and time are controlled within the above ranges, which helps to improve the smelting efficiency. Preferably, the refining temperature and time are controlled within the above ranges, which helps to further reduce the content of impurities in the melt. Preferably, the atomization temperature, time, pressure and speed are controlled within the above ranges, which helps to obtain Er-Zr microalloyed AlSi10Mg alloy powder with suitable sphericity and particle size distribution, so that the Er-Zr microalloyed AlSi10Mg alloy powder yield is 36% to 38%, which helps to further improve the density of aluminum alloy parts, thereby helping to further improve the mechanical properties of aluminum alloy parts.

[0037] In one embodiment of the present application, the atomizing gas is argon, and the nozzle diameter used is 5 mm.

[0038] In one embodiment of the present application, the preparation method further comprises pouring the atomized product into an ultrasonic vibration screen to screen powders of different particle sizes to obtain Er-Zr micro-alloyed AlSi10Mg alloy powder.

[0039] In one embodiment of the present application, the preparation method further includes first manually washing the furnace before adding materials, wiping the inner wall of the gas atomization device, the crucible and the tundish with ethanol to avoid the introduction of impurity elements and reduce the influence of moisture in the smelting furnace on the smelting process. After the furnace washing is completed, the required corresponding raw materials pure aluminum, pure magnesium, aluminum silicon master alloy, aluminum erbium master alloy and aluminum zirconium master alloy are weighed according to the component content design, and placed in the crucible. The material follows the principle of sparse upper and dense lower to prevent the bridging effect from affecting the final composition. In addition, considering the burning loss of pure magnesium, mass compensation is required, that is, 5% more mass is added according to the designed component content. Sealing test. When the vacuum degree of the smelting chamber and the atomization chamber reaches about 50Pa, it can be considered that the airtightness meets the standard. Under this condition, one is to prevent the oxidation of aluminum alloy, and the other is to ensure the low oxygen and nitrogen content of the final product, so that the product quality meets the standard. After the vacuum degree meets the standard, high-purity argon gas is used for gas replacement, and then smelting is carried out.

[0040] In another typical embodiment of the present application, a method for preparing an aluminum alloy part is provided, the method comprising: sequentially 3D printing and heat treating the aforementioned Er-Zr microalloyed AlSi10Mg alloy powder to obtain an aluminum alloy part.

[0041] The Er-Zr micro-alloyed AlSi10Mg alloy powder is printed and heat treated by laser selective melting additive manufacturing (SLM) technology, and the prepared aluminum alloy parts have strong mechanical properties.

[0042] In order to improve the density of aluminum alloy parts, in one embodiment of the present application, the pressure of the above-mentioned 3D printing is preferably 23mbar~27mbar; and / or, the fan flow rate of 3D printing is 2.3m / s~2.7m / s; and / or, the preheating temperature of the substrate for 3D printing is 80~120℃; and / or, the thickness between the printed layers of 3D printing is 20~50μm; and / or, the laser scanning spacing of 3D printing is 100~120μm; and / or, the interlayer rotation angle of 3D printing is 67°; and / or, the laser scanning power of 3D printing is 260W~340W; and / or, the laser scanning speed of 3D printing is 1400mm / s~1800mm / s; and / or, 3D printing is carried out in an atmosphere with an oxygen content not exceeding 0.08%.

[0043] In order to improve the stability of aluminum alloy parts, in one embodiment of the present application, the temperature of the heat treatment is preferably 165° C. to 280° C.; and / or the holding time of the heat treatment is 2 h to 4 h.

[0044] In one embodiment of the present application, the density of the print obtained by 3D printing is not less than 99.95%; and / or the tensile strength of the print is 451.6MPa~482.7MPa; and / or the yield strength of the print is 293.4MPa~329.7MPa; and / or the elongation of the print is 4.1%~8.7%.

[0045] Printed parts with the above-mentioned density, tensile strength, yield strength and elongation are helpful for preparing aluminum alloy parts with strong mechanical properties.

[0046] In another typical embodiment of the present application, an aluminum alloy part is provided. The aluminum alloy part is prepared by the aforementioned preparation method.

[0047] In one embodiment of the present application, the tensile strength of the above-mentioned aluminum alloy part is 321.6MPa~483.0MPa; and / or, the yield strength of the aluminum alloy part is 210.2MPa~311.0MPa; and / or, the elongation of the aluminum alloy part is 6.9%~19.5%.

[0048] The aluminum alloy product having the above tensile strength, yield strength and elongation has a higher bearing stress and a wider range of applications.

[0049] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.

[0050] Example 1

[0051] First, the furnace is manually cleaned, and the inner wall of the gas atomization device, the crucible and the intermediate package are wiped with ethanol to avoid the introduction of impurity elements and reduce the influence of moisture in the smelting furnace on the smelting process. After the furnace is cleaned, 7665g of pure aluminum, 141.75g ​​of pure magnesium, 15000g of aluminum silicon master alloy, 4800g of aluminum erbium master alloy and 2400g of aluminum zirconium master alloy are placed in the crucible according to the principle of top sparse and bottom dense. Among them, the mass content of silicon in the aluminum silicon master alloy is 20%, the mass content of erbium in the aluminum erbium master alloy is 5%, and the mass content of zirconium in the aluminum zirconium master alloy is 10%. Then the sealing test is carried out. When the vacuum degree of the smelting chamber and the atomization chamber reaches about 50Pa, the airtightness meets the standard, and high-purity argon gas is used for gas replacement.

[0052] Next, the alloy is melted, refined and atomized. The temperature and time during the melting process are 850℃ and 20min respectively, and the refining temperature and time are 850℃ and 15min respectively. Then the aluminum alloy melt after melting and refining is poured into the tundish step by step and gas atomized to make powder. The conditions for atomization powder making are: argon is used as the atomizing gas, the atomizing gas pressure is 2.5MPa, the atomizing temperature is 850℃, the atomizing nozzle diameter is 5mm, and the atomizing speed is 10Kg / min. After atomization is completed, the powder is cooled down and the powder making is completed. The obtained powder is poured into an ultrasonic vibration screen for particle size screening to obtain Er-Zr microalloyed AlSi10Mg alloy powder. The volume fraction of Er-Zr microalloyed AlSi10Mg alloy powder in the particle size range of 0~75μm is 97.62%, and D10 is 22.3μm, D50 is 37.8μm and D90 is 62.1μm, and the powder yield is 38%. In terms of mass percentage, the Si content in the Er-Zr microalloyed AlSi10Mg alloy powder is 10.58%, the Mg content is 0.41%, the Er content is 0.73%, the Zr content is 0.70%, the total content of inevitable impurities is ≤0.15wt%, the content of a single impurity is less than 0.05wt%, the balance is Al element, the oxygen content is 420ppm, the N content is 11ppm, the sphericity is 81.4%, and the hollow powder rate is 0.43%.

[0053] The Er-Zr microalloyed AlSi10Mg alloy powder prepared above was printed by laser selective melting additive manufacturing technology to obtain a printed part. The specific process parameters are: the oxygen content of the printing chamber is 0.08%, the pressure of the printing chamber is 25mbar, the fan flow rate is 2.5m / s, the substrate preheating temperature is 80℃, the thickness between printing layers is 30μm, the scanning spacing is 100μm, the interlayer rotation angle is 67°, the scanning power is 260W and the scanning speed is 1500mm / s. Based on the above parameter control, the density of the printed part is 99.98%, and there are no crack defects in the organization.

[0054] The printed part was kept at 280°C for 2 hours to obtain an aluminum alloy part.

[0055] Example 2

[0056] First, the furnace is manually cleaned, and the inner wall of the gas atomization device, the crucible and the intermediate package are wiped with ethanol to avoid the introduction of impurity elements and reduce the influence of moisture in the smelting furnace on the smelting process. After the furnace is cleaned, 5265g of pure aluminum, 141.75g ​​of pure magnesium, 15000g of aluminum silicon master alloy, 7200g of aluminum erbium master alloy and 2400g of aluminum zirconium master alloy are placed in the crucible according to the principle of top sparse and bottom dense. Among them, the mass content of silicon in the aluminum silicon master alloy is 20%, the mass content of erbium in the aluminum erbium master alloy is 5%, and the mass content of zirconium in the aluminum zirconium master alloy is 10%. Then the sealing test is carried out. When the vacuum degree of the smelting chamber and the atomization chamber reaches about 50Pa, the airtightness meets the standard, and high-purity argon gas is used for gas replacement.

[0057] Next, the alloy is smelted, refined and atomized. The temperature and time during the smelting process are 900℃ and 20min respectively, and the refining temperature and time are 900℃ and 15min respectively. Subsequently, the aluminum alloy melt after smelting and refining is poured into the tundish step by step and gas atomized for powder making. The conditions for atomization powder making are: argon is used as the atomizing gas, the atomizing gas pressure is 2.5MPa, the atomizing temperature is 850℃, the atomizing nozzle diameter is 5mm, and the atomizing speed is 10Kg / min. After the atomization is completed, wait for the powder to cool down, complete the powder making, and pour the obtained powder into the ultrasonic vibration sieve for particle size screening to obtain Er-Zr microalloyed AlSi10Mg alloy powder. The volume fraction of the target powder in the particle size range of 0~75μm is 97.83%, and D10 is 21.9μm, D50 is 37.5μm and D90 is 61.8μm, and the powder yield is 36%. In terms of mass percentage, the Si content of the prepared Er-Zr microalloyed AlSi10Mg alloy powder is 10.54%, the Mg content is 0.42%, the Er content is 1.14%, the Zr content is 0.74%, the total content of inevitable impurities is ≤0.15wt%, the content of a single impurity is less than 0.05wt%, the balance is Al element, the oxygen content is 404ppm, the N content is 13ppm, the sphericity is 83.5%, and the hollow powder rate is 0.54%.

[0058] The Er-Zr microalloyed AlSi10Mg alloy powder prepared above was printed by laser selective melting additive manufacturing technology to obtain a printed part. The specific process parameters are: the oxygen content of the printing chamber is 0.08%, the pressure of the printing chamber is 25mbar, the fan flow rate is 2.5m / s, the substrate preheating temperature is 80℃, the thickness between printing layers is 30μm, the scanning spacing is 100μm, the interlayer rotation angle is 67°, the scanning power is 320W and the scanning speed is 1600mm / s. Based on the above parameter control, the density of the printed part is 99.97%, and there are no crack defects in the organization.

[0059] The printed part was kept at 165°C for 4 hours to obtain an aluminum alloy part.

[0060] Example 3

[0061] The difference from Example 1 is that the content of Er element is 0.70%, the content of Zr element is 0.70%, the mass ratio of Er element to Zr element is 1:1, and finally an aluminum alloy product is obtained.

[0062] Example 4

[0063] The difference from Example 1 is that the content of Er element is 1.08%, the content of Zr element is 0.70%, the mass ratio of Er element to Zr element is 1:0.65, and finally an aluminum alloy product is obtained.

[0064] Example 5

[0065] The difference from Example 1 is that the content of Er element is 1.30%, the content of Zr element is 0.70%, the mass ratio of Er element to Zr element is 1:0.54, and finally an aluminum alloy product is obtained.

[0066] Example 6

[0067] The difference from Example 1 is that the content of Si element is 10.60%, the content of Mg element is 0.35%, the content of Er element is 1.30%, and the content of Zr element is 0.7%, and finally an aluminum alloy part is obtained.

[0068] Example 7

[0069] The difference from Example 1 is that the content of Si element is 9.50%, the content of Mg element is 0.55%, the content of Er element is 0.70%, and the content of Zr element is 1.30%, and finally an aluminum alloy product is obtained.

[0070] Example 8

[0071] The difference from Example 1 is that the melting temperature is 850° C., the melting time is 30 min, the refining temperature is 850° C., the refining time is 15 min, and finally an aluminum alloy product is obtained.

[0072] Example 9

[0073] The difference from Example 1 is that the melting temperature is 950° C., the melting time is 15 min, the refining temperature is 950° C., the refining time is 10 min, and finally an aluminum alloy product is obtained.

[0074] Example 10

[0075] The difference from Example 1 is that the melting temperature is 1000° C., the melting time is 10, the refining temperature is 1000° C., the refining time is 5 min, and finally an aluminum alloy product is obtained.

[0076] Embodiment 11

[0077] The difference from Example 1 is that the atomization temperature is 850°C, the atomization pressure is 2.8MPa, the atomization speed is 10Kg / min, and an aluminum alloy product is finally obtained. Among them, the sphericity of the Er-Zr microalloyed AlSi10Mg alloy powder is 82.7%, the hollow powder rate of the Er-Zr microalloyed AlSi10Mg alloy powder is 0.40%, the volume fraction of the Er-Zr microalloyed AlSi10Mg alloy powder in the particle size range of 0~75μm is 98.13%, and the D10 of the Er-Zr microalloyed AlSi10Mg alloy powder is 22.8μm, D50 is 37.7μm and D90 is 62.0μm.

[0078] Example 12

[0079] The difference from Example 1 is that the atomization temperature is 900°C, the atomization pressure is 2.3 MPa, and an aluminum alloy product is finally obtained. Among them, the sphericity of the Er-Zr microalloyed AlSi10Mg alloy powder is 80.1%, the hollow powder rate of the Er-Zr microalloyed AlSi10Mg alloy powder is 0.41%, the volume fraction of the Er-Zr microalloyed AlSi10Mg alloy powder in the particle size range of 0~75μm is 97.68, and the D10 of the Er-Zr microalloyed AlSi10Mg alloy powder is 23.1μm, D50 is 37.4μm and D90 is 61.9μm.

[0080] Example 13

[0081] The difference from Example 1 is that the atomization temperature is 950°C, the atomization pressure is 3.0 MPa, and an aluminum alloy product is finally obtained. Among them, the sphericity of the Er-Zr microalloyed AlSi10Mg alloy powder is 79.3%, the hollow powder rate of the Er-Zr microalloyed AlSi10Mg alloy powder is 0.59%, the volume fraction of the Er-Zr microalloyed AlSi10Mg alloy powder in the particle size range of 0~75μm is 97.21, and the D10 of the Er-Zr microalloyed AlSi10Mg alloy powder is 26.4.μm, D50 is 38.21μm and D90 is 64.22μm.

[0082] Embodiment 14

[0083] The difference from Example 1 is that the 3D printing pressure is 23 mbar, the 3D printing fan flow rate is 2.7 m / s, and finally an aluminum alloy part is obtained.

[0084] Embodiment 15

[0085] The difference from Example 1 is that the 3D printing pressure is 27 mbar, the 3D printing fan flow rate is 2.3 m / s, and finally an aluminum alloy part is obtained.

[0086] Example 16

[0087] The difference from Example 1 is that the 3D printing pressure is 30 mbar, the 3D printing fan flow rate is 3.0 m / s, and finally an aluminum alloy part is obtained.

[0088] Embodiment 17

[0089] The difference from Example 1 is that the preheating temperature of the substrate for 3D printing is 120° C., the thickness between the printed layers for 3D printing is 50 μm, the laser scanning spacing for 3D printing is 120 μm, and finally an aluminum alloy part is obtained.

[0090] Embodiment 18

[0091] The difference from Example 1 is that the laser scanning power of 3D printing is 340 W, the laser scanning speed of 3D printing is 1800 mm / s, and finally an aluminum alloy part is obtained.

[0092] Embodiment 19

[0093] The difference from Example 1 is that the laser scanning power of 3D printing is 260 W, the laser scanning speed of 3D printing is 1400 mm / s, and finally an aluminum alloy part is obtained.

[0094] Embodiment 20

[0095] The difference from Example 1 is that the laser scanning power of 3D printing is 250 W, the laser scanning speed of 3D printing is 1300 mm / s, and finally an aluminum alloy part is obtained.

[0096] Comparative Example 1

[0097] The difference from Example 1 is that the content of Si element is 11.60%, the content of Mg element is 0.25%, the content of Er element is 1.50%, and the content of Zr element is 0.50%, and finally an aluminum alloy product is obtained.

[0098] Performance Testing

[0099] The tensile strength, yield strength and elongation are tested according to GB / T 228.1-2010.

[0100] The printed parts prepared in the examples and comparative examples were tested for tensile strength, yield strength and elongation. The test results are shown in Table 1.

[0101] The aluminum alloy parts prepared in the examples and comparative examples were tested for tensile strength, yield strength and elongation. The test results are shown in Table 2.

[0102] Table 1

[0103]

[0104] Table 2

[0105]

[0106] Figure 1 This is a SEM image of the Er-Zr microalloyed AlSi10Mg alloy powder in Example 1 of the present application. Figure 1 It can be seen that the Er-Zr microalloyed AlSi10Mg alloy powder is a spherical material with regular structure.

[0107] Figure 2 This is the SEM image of the Er-Zr microalloyed AlSi10Mg alloy powder in Example 2 of the present application. Figure 2 It can be seen that the Er-Zr microalloyed AlSi10Mg alloy powder has a high size uniformity.

[0108] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0109] In the Er-Zr microalloyed AlSi10Mg alloy powder of the present application, the contents of Si element, Mg element, Er element and Zr element are controlled within a suitable range, which helps to improve the mechanical properties of the aluminum alloy parts finally formed, especially the content of Er element is controlled at 0.70~1.30%, the content of Zr element is controlled at 0.70~1.30%, the rare earth element Er has a small solid solubility in the Al matrix, and is repelled to the front end of the solid-liquid interface during the crystallization process, resulting in enrichment. The enrichment of the rare earth element Er at the solid-liquid interface helps to reduce the probability of Si and Mg atoms entering the solid solution, thereby helping to inhibit the growth of the unit cell. In addition, the Er element enriched at the front end of the solid-liquid interface reacts eutectically with Al to form Al3Er phase during the subsequent solidification process. At the same time, the smaller solid solubility of Er in the aluminum matrix shows that Al3Er has a stronger precipitation driving force, so that it can precipitate a larger volume fraction. The Al3Er phase has a high melting point and will not completely melt during the remelting process at a relatively low temperature at the molten pool boundary. It can act as a heterogeneous nucleation point to promote the formation of equiaxed crystals and refine grains, thereby helping to improve the tensile strength, yield strength and elongation of aluminum alloy parts. The Zr element can form a kinetically stable L12Al3 (Er, Zr) phase with the Er element, which has a second phase strengthening effect and a recrystallization inhibition effect, thereby helping to further improve the mechanical properties of aluminum alloy parts.

[0110] The above are only embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An Er-Zr microalloyed AlSi10Mg alloy powder, characterized in that: In terms of mass percentage, the Er-Zr microalloyed AlSi10Mg alloy powder includes the following elements: Si element content is 9.50-10.60%, Mg element content is 0.35-0.55%, Er element content is 0.70-1.30%, Zr element content is 0.70-1.30%, the total content of inevitable impurities is ≤0.15wt%, the content of a single impurity is less than 0.05wt%, and the balance is Al element.

2. The Er-Zr microalloyed AlSi10Mg alloy powder according to claim 1, characterized in that: The mass ratio of the Er element to the Zr element is 1:0.65-1; And / or, the content of oxygen in the Er-Zr microalloyed AlSi10Mg alloy powder is ≤460ppm; and / or, the content of nitrogen in the Er-Zr microalloyed AlSi10Mg alloy powder is ≤15ppm; and / or, the sphericity of the Er-Zr microalloyed AlSi10Mg alloy powder is ≥80%; and / or, the hollow powder rate of the Er-Zr microalloyed AlSi10Mg alloy powder is ≤0.54%; And / or, the volume fraction of the Er-Zr microalloyed AlSi10Mg alloy powder in the particle size range of 0-75 μm is greater than 97%, and the D10 of the Er-Zr microalloyed AlSi10Mg alloy powder is 20-27 μm, the D50 is 35-40 μm and the D90 is 60-67 μm.

3. A method for preparing the Er-Zr microalloyed AlSi10Mg alloy powder according to claim 1 or 2, characterized in that: The preparation method comprises: The raw materials including metals are melted, refined and atomized in sequence according to the proportions to obtain the Er-Zr micro-alloyed AlSi10Mg alloy powder.

4. The preparation method according to claim 3, characterized in that: The smelting temperature is 850°C to 950°C; and / or the smelting time is 15min to 30min; And / or, the refining temperature is 850°C to 950°C; and / or, the refining time is 10min to 15min; And / or, the atomization temperature is 850°C to 900°C; and / or, the atomization pressure is 2.3MPa to 2.8MPa; and / or, the atomization speed is 10 to 14Kg / min.

5. A method for preparing an aluminum alloy part, characterized in that: The preparation method comprises: The Er-Zr microalloyed AlSi10Mg alloy powder according to claim 1 or 2 is subjected to 3D printing and heat treatment in sequence to obtain the aluminum alloy product.

6. The preparation method according to claim 5, characterized in that: The pressure of the 3D printing is 23mbar~27mbar; and / or, the fan flow rate of the 3D printing is 2.3m / s~2.7m / s; and / or, the preheating temperature of the substrate of the 3D printing is 80~120℃; and / or, the interlayer thickness of the 3D printing is 20-50 μm; and / or, the laser scanning spacing of the 3D printing is 100-120 μm; and / or, the interlayer rotation angle of the 3D printing is 67°; and / or, the laser scanning power of the 3D printing is 260W-340W; and / or, the laser scanning speed of the 3D printing is 1400mm / s-1800mm / s; And / or, the 3D printing is performed in an atmosphere with an oxygen content not exceeding 0.08%.

7. The preparation method according to claim 5, characterized in that: The temperature of the heat treatment is 165° C. to 280° C.; and / or the insulation time of the heat treatment is 2 h to 4 h.

8. The preparation method according to claim 5, characterized in that: The printout obtained by the 3D printing has a density of not less than 99.95%; and / or, a tensile strength of the printout is 451.6 MPa to 482.7 MPa; and / or, a yield strength of the printout is 293.4 MPa to 329.7 MPa; and / or, an elongation of the printout is 4.1% to 8.7%.

9. An aluminum alloy part, characterized in that: The aluminum alloy product is prepared by the preparation method described in any one of claims 5 to 8.

10. The aluminum alloy product according to claim 9, characterized in that: The tensile strength of the aluminum alloy part is 321.6 MPa to 483.0 MPa; and / or, the yield strength of the aluminum alloy part is 210.2 MPa to 311.0 MPa; and / or, the elongation of the aluminum alloy part is 6.9% to 19.5%.

Citation Information

Patent Citations

  • Rare earth erbium element reinforced AlSi10Mg aluminum alloy powder special for SLM and application thereof

    CN108396203A

  • Additive manufacturing high-strength aluminum alloy powder, and preparation method and application thereof

    CN111496244A

  • High-toughness AlCrSc alloy powder for 3D printing and preparation method and application thereof

    CN113512671A

  • Method for preparing high-strength Al-Si-Mg alloy through laser powder bed fusion technology

    CN116590558A

  • High-strength aluminum alloy powder for 3D printing and preparation method for high-strength aluminum alloy powder

    WO2023019697A1

Cited By

  • Aluminum alloy powder, preparation method of aluminum alloy powder, aluminum alloy workpiece and preparation method of aluminum alloy workpiece

    CN121607619A